UNIVERSİTY STUDENTS' VIEWS ON HIGH-RISE BUILDINGS AND SKYSCRAPERS (Third Sector Social Economic Review, 2018)
Since the second half of the eighteenth century, the invention of cement and the use of steel in construction have made it possible to build multi-storey buildings. The high-rise buildings initially built in the United States then rapidly spreaded in Europe and other countries around the world. The high-rise buildings and skyscrapers that are the subject of debate from the moment they emerge, have begun to dominate Turkish cities in the aftermath of the rapid urbanization process in Turkey. The focus of these discussions is on urban aesthetics and social relations. This text is based on the answers given to the question of “generate ideas about high-rise buildings and skyscrapers that are rapidly spreading in our big cities” which is one of the questions given in the final exam to the students of Chemical Engineering Department for the course “TOS 208- Social Structure of Turkey”.  In this text, the opinions and attitudes reflected on the written examination papers of the sixty-eight students who have taken the exam will be classified and evaluated.
Keywords: University students; urbanization; high-rise buildings; multi- storey buildings; skyscraper